The Effectiveness of Using Animated Infographic Technology in Developing Visual Thinking Skills of Seventh Grade Students in science course - Al-Harthi, Bashayer Mubarak; Al-Ghamdi, Shahid Abdullah; Filmban, Fadwa Yassin (Journal of Curriculum and Teaching Methodology, 2025)
The research aimed to identify the effectiveness of teaching using animated infographic technology in developing visual thinking skills in science course among females in seventh grade students. The research used the experimental approach of one group, and the research sample consisted of seventh grade students at the school Al-Sayeda Khadija bent Khuwaylid to memorize the Holy Quran in Al Baha. To achieve the objectives of the research, a set of videos was designed in the way of animated infographics. The research tool consisted of a pre-and-post test of visual thinking skills. The results showed that there are statistically significant differences between the average scores of students in the pre- and post-which indicated the effectiveness of teaching using animated infographic technology in developing visual thinking skills as a whole and in visual discrimination skill, deriving meanings skill, and Information analysis skill separately. In the light of the research results, a set of proposed recommendations was made to activate the use of animated infographics in teaching.
Keywords: Animated Infographic; Visual Thinking Skills; Deriving Meanings Skill; Visual Discrimination Skill; Information Analysis Skill